Can people afford to pay for health care? - New evidence on financial protection in Finland (2021) - Tervola Jussi; Aaltonen Katri; Tallgren Fanny (World Health Organization, WHO, 2022)
This review is part of a series of country-based studies generating new
evidence on financial protection in health systems in Europe. Financial
protection is central to universal health coverage and a core dimension
of health system performance. The incidence of catastrophic health
spending in Finland is relatively high compared to other Nordic countries.
It is driven mainly by out-of-pocket payments for outpatient medicines,
followed by outpatient care and dental care. Unmet need for health
and dental services is also more prevalent in Finland than in many other
countries in western Europe. The factors that undermine access and
financial protection, with a disproportionate impact on poorer and older
households, include: long-standing issues in the governance of coverage
policy – multiple and overlapping coverage schemes, combined with
regional variation in waiting times and co-payments, favour people in
work and wealthier households; complex and heavy co-payments for
almost all health services, with inadequate protection mechanisms; gaps
in coverage and weaknesses in purchasing outpatient medicines; and
relatively low levels of public investment in health. To reduce unmet need
and financial hardship, policy should focus on limiting co-payments for
outpatient care, especially primary care; improving protection from all
co-payments for poorer households and people with high need for health
care; and strengthening supply-side policies to promote better prescribing,
dispensing and use of medicines.